Peningkatan Kinerja Guru Melalui Supervisi Klinis Pada Guru-Guru Di SMK Negeri 1 Kodi Utara Tahun Pelajaran 2023/2024 - Seingo, Charles (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This action research aims to evaluate the work motivation of teachers at SMK Negeri 1 Kodi Utara, focusing on the effectiveness of internal communication and the professionalism of the school principal's leadership. The research results indicate a significant increase in teacher work motivation from the pre-cycle stage to cycle II. In the pre-cycle stage, the average teacher work motivation reached 69.20, with a completeness percentage of 36.96%. Following the implementation of actions in cycle I, teacher work motivation increased to 75.73, with a completeness percentage of 65.22% and an incompleteness percentage of 34.78%. In cycle II, the average teacher work motivation reached 82.27, with the completeness percentage significantly rising to 89.13% and the incompleteness percentage dropping to 10.87%. Thus, this research indicates a continuous improvement in teacher work motivation throughout the study. The results show that enhancing internal communication and the professionalism of the school principal's leadership positively influenced teacher work motivation. The impact of this increase is reflected in improved teaching quality and a more positive contribution from teachers to student development. In conclusion, this research highlights the importance of effective internal communication and school leadership in improving teacher work motivation. These efforts result in positive changes in the school learning environment. The findings confirm that appropriate support and well-planned strategies play a crucial role in enhancing work and learning quality in educational institutions.